1996
DOI: 10.1007/bf00040996
|View full text |Cite
|
Sign up to set email alerts
|

The purple bacterial photosynthetic unit

Abstract: Now is a very exciting time for researchers in the area of the primary reactions of purple bacterial photosynthesis. Detailed structural information is now available for not only the reaction center (Lancaster et al. 1995, in: Blankenship RE et al. (eds) Anoxygenic Photosynthetic Bacteria, pp 503-526), but also LH2 from Rhodopseudomonas acidophila (McDermott et al. 1995, Nature 374: 517-521) and LH1 from Rhodospirillum rubrum (Karrasch et al. 1995. EMBO J 14: 631-638). These structures can now be integrated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
73
0
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 32 publications
0
73
0
4
Order By: Relevance
“…Myllykallio et al (66) suggested that the important difference was that of the length of the linker connecting the cyt c head with the anchor. From the structures of the bc 1 complex and cytochrome oxidase dimers and from a model of the reaction center with LH1 in position (67,68), the closest approach between reaction partners can be estimated. The main difference between the electron transfer from the bc 1 complex to the reaction center (∼87 Å distance for nearest approach between donor and acceptor centers) and that to cytochrome oxidase (∼54 Å distance of closest approach) is the presence of a cylindrical barrier of the LH1 light-harvesting complex, which separates the reaction center protein from its neighbors in the membrane by an additional ∼23 Å.…”
Section: Mobility and Binding Of The Isp: Complementary Functional Asmentioning
confidence: 99%
“…Myllykallio et al (66) suggested that the important difference was that of the length of the linker connecting the cyt c head with the anchor. From the structures of the bc 1 complex and cytochrome oxidase dimers and from a model of the reaction center with LH1 in position (67,68), the closest approach between reaction partners can be estimated. The main difference between the electron transfer from the bc 1 complex to the reaction center (∼87 Å distance for nearest approach between donor and acceptor centers) and that to cytochrome oxidase (∼54 Å distance of closest approach) is the presence of a cylindrical barrier of the LH1 light-harvesting complex, which separates the reaction center protein from its neighbors in the membrane by an additional ∼23 Å.…”
Section: Mobility and Binding Of The Isp: Complementary Functional Asmentioning
confidence: 99%
“…How does UQH 2 escape from such a core complex? There are two possible solutions: either the LH1 ring is not complete, i.e., there is a gap, or the LH1 structure is inherently f lexible enough to allow UQH 2 to diffuse through it (7)(8)(9).…”
mentioning
confidence: 99%
“…To explain the cooperative action of these chlorophylls, Emerson and Arnold postulated that only very few chlorophylls in the primary reaction site, termed the photosynthetic reaction center (RC), directly take part in photochemical reactions; most chlorophylls serve as lightharvesting antennae by capturing the sunlight and funneling electronic excitation toward the RC. This notion gave rise to the definition of the photosynthetic unit (PSU) as an ensemble of an RC with associated light-harvesting complexes containing up to 250 chlorophylls, and became widely accepted only when Duysens carried out a critical experiment in which energy transfer between different chlorophylls was observed (3).A wealth of accumulated evidence proves that the organization of PSUs, to surround an RC with aggregates of chlorophylls and associated carotenoids, is universal in both photosynthetic bacteria and higher plants (2,(4)(5)(6).Of the known photosynthetic systems, the PSU of purple bacteria is the most studied and best characterized. Fig.…”
mentioning
confidence: 99%
“…A wealth of accumulated evidence proves that the organization of PSUs, to surround an RC with aggregates of chlorophylls and associated carotenoids, is universal in both photosynthetic bacteria and higher plants (2,(4)(5)(6).…”
mentioning
confidence: 99%